Application Dissolved Oxygen (DO) For Water Quality Monitoring of Shrimp Ponds With IoT (Internet of Things) - Imam Abdul Rozaq (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
Water is a very important requirement, both for humans and other living things such as fish and plants[1][2][3]. In the fields of agriculture, fisheries, and the fresh water management industry is very important to improve quality. [4]. In its development, the demand for fish and seafood (shrimp, squid, etc.) increases so that to meet these demands, it is necessary to pay attention to the quality of the pond water that will be used to breed fish and seafood). The method used in this study is Research and Development (RnD). This research can produce readings using cayenne.mydevice.com one of the Internet providers of things with communication web Internet of thing message queue telemetry transport (MQTT)[12]. This research was conducted at the “Balai Besar Perikanan Budidaya Air Payau (BBPBAP)”. The parameters studied were sensor accuracy, system constraints and the application website. Conclusion this research is (1) the average sensor accuracy is good, namely 88.86%. (2) there are two obstacles faced, namely sensor maintenance and storage and (3) monitoring the data in live, minute, hour, day, week, month, 3 months, 6 months and 1 year.